Maya Angelou, Richard Wright and American Autobiography - Šabartová, Naďa (Univerzita Pardubice, 2018)
The thesis depicts the American autobiography, its history, and purpose with an emphasis on the Afro-American autobiography. It tries to answer the questions concerning autobiography and it analyses two autobiographical works by Afro-American writers. It mentions the elements of autobiography and compares the lives of the authors from the view of the racial relationship depiction and the demonstration of the Afro-American community specifics.
Maya Angelou, Richard Wright a americká autobiografie
Keywords: autobiografie; segregace; rasismus; Black Boy; Wright, Richard; I Know Why the Caged Bird Sings; Angelou, Maya; afroamerická literatura; autobiography; segregation; racism; Black Boy; Wright, Richard; I Know Why the Caged Bird Sings; Angelou, Maya; Afro-American literature